Etiology of combined pituitary hormone deficiency: GNAO1 as a novel candidate gene - Plachy, Lukas; Dusatkova, Petra; Maratova, Klara; Amaratunga, Shenali Anne; Zemkova, Dana; Neuman, Vit; Kolouskova, Stanislava; Obermannova, Barbora; Snajderova, Marta; Sumnik, Zdenek; Lebl, Jan; Pruhova, Stepanka (Endocrine connections, 2024)
Because the causes of combined pituitary hormone deficiency (CPHD) are complex, the etiology of congenital CPHD remains unknown in most cases. The aim of the study was to identify the genetic etiology of CPHD in a well-defined single-center cohort. In total, 34 children (12 girls) with congenital CPHD (growth hormone (GH) deficiency and impaired secretion of at least one other pituitary hormone) treated with GH in our center were enrolled in the study. Their median age was 11.2 years, pre-treatment height was -3.2 s.d., and maximal stimulated GH was 1.4 ug/L. Of them, 30 had central adrenal insufficiency, 27 had central hypothyroidism, ten had hypogonadotropic hypogonadism, and three had central diabetes insipidus. Twenty-six children had a midline defect on MRI. Children with clinical suspicion of a specific genetic disorder underwent genetic examination of the gene(s) of interest via Sanger sequencing or array comparative genomic hybridization. Children without a detected causal variant after the first-tier testing or with no suspicion of a specific genetic disorder were subsequently examined using next-generation sequencing growth panel. Variants were evaluated by the American College of Medical Genetics standards. Genetic etiology was confirmed in 7/34 (21%) children. Chromosomal aberrations were found in one child (14q microdeletion involving the OTX2 gene). The remaining 6 children had causative genetic variants in the GLI2, PROP1, POU1F1, TBX3, PMM2, and GNAO1 genes, respectively. We elucidated the cause of CPHD in a fifth of the patients. Moreover, our study supports the PMM2 gene as a candidate gene for CPHD and suggests pathogenic variants in the GNAO1 gene as a potential novel genetic cause of CPHD.
Keywords: combined pituitary hormone deficiency; next-generation sequencing; genetics of short stature; short stature; growth hormone deficiency